P288 Vedolizumab May Be An Effective Option For The Management Of Postoperative Recurrence Of Crohn's Disease. (27th May 2021) - Macaluso, F S; Cappello, M; Crispino, F; Grova, M; Privitera, A C; Piccillo, G; Magnano, A; Ferracane, C; Belluardo, N; Giangreco, E; Fries, W; Viola, A; et al.
Abstract: Background: The role of Vedolizumab (VDZ) as therapeutic option for the postoperative recurrence of Crohn's disease (CD) following ileocolonic resection is currently unknown. We aimed to assess the effectiveness of VDZ in this setting. Methods: All consecutive CD patients with an available baseline colonoscopy at 6-12 months from the ileocolonic resection and treated with VDZ for the postoperative recurrence after the baseline colonoscopy were extracted from the cohort of the Sicilian Network for Inflammatory Bowel Diseases (SN-IBD). The primary outcome was endoscopic success, assessed at the first colonoscopy following initiation of VDZ. In patients with Rutgeerts score i0 or i1 at baseline, endoscopic success was defined by maintenance of Rutgeerts score i0 or i1; in patients with Rutgeerts score ≥ i2 at baseline, it was defined as reduction of at least one point of Rutgeerts score. The secondary outcome was clinical failure, assessed at one year and at the end of follow-up. Results: Seventy patients were included (median follow-up: 23.5 months). All 9 patients without endoscopic recurrence at baseline (Rutgeerts score i0 or i1) and available post-treatment colonoscopy maintained a Rutgeerts score i0 or i1 (treatment success: 100%). In patients with endoscopic recurrence (Rutgeerts score ≥ i2 at baseline), a reduction of at least one point in the Rutgeerts score was obtained in 20 out of 42 patients (47.6%). By combining the two subgroups, the overall endoscopic success was achieved in 29 out of 51 patients (56.9%). Furthermore, 14 out of 42 patients (33.3%) with endoscopic recurrence at baseline achieved a Rutgeerts score i0 or i1 at the subsequent colonoscopy. Clinical failure was reported in 13/70 patients (18.6%) at one year, and in 23/70 patients (32.9%) at the end of follow-up. A new resection was required in 7/70 patients (10.0%). Conclusion: VDZ may be a therapeutic option for the management of postoperative recurrence of CD. Further studies are needed to confirm these results.